2022
DOI: 10.3389/fcell.2022.993257
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and coordination of the different DNA damage responses in Drosophila

Abstract: Cells have evolved mechanisms that allow them to respond to DNA damage to preserve genomic integrity and maintain tissue homeostasis. These responses include the activation of the cell cycle checkpoints and the repair mechanisms or the induction of apoptosis that eventually will eliminate damaged cells. These “life” vs. “death” decisions differ depending on the cell type, stages of development, and the proliferation status of the cell. The apoptotic response after DNA damage is of special interest as defects i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 122 publications
1
14
0
Order By: Relevance
“…Because CifAB-expressing CI males suffer from depleted lncRNA and enhanced DNA damage, resulting in sperm development with altered H-P abundance, we next investigated whether fertilization by the compromised CI sperm causes adverse effects in embryos during nuclear divisions. Previous studies showed that Drosophila embryonic DNA damage is only evident in late stages of development ~6 hours after egg deposition (AED) toward gastrulation (33)(34)(35), as the cells at this stage become hyperprolifertive, and hence, more susceptible to damage (36)(37)(38). Although CI is often associated with a first-mitotic division defect within 1 hour of egg fertilization, additional developmental defects also occur in late CI embryos developing through the preblastoderm divisions, syncytial, and cellularized blastoderms (10,(39)(40)(41).…”
Section: Embryos Succumb To Dna Damagementioning
confidence: 99%
“…Because CifAB-expressing CI males suffer from depleted lncRNA and enhanced DNA damage, resulting in sperm development with altered H-P abundance, we next investigated whether fertilization by the compromised CI sperm causes adverse effects in embryos during nuclear divisions. Previous studies showed that Drosophila embryonic DNA damage is only evident in late stages of development ~6 hours after egg deposition (AED) toward gastrulation (33)(34)(35), as the cells at this stage become hyperprolifertive, and hence, more susceptible to damage (36)(37)(38). Although CI is often associated with a first-mitotic division defect within 1 hour of egg fertilization, additional developmental defects also occur in late CI embryos developing through the preblastoderm divisions, syncytial, and cellularized blastoderms (10,(39)(40)(41).…”
Section: Embryos Succumb To Dna Damagementioning
confidence: 99%
“…This complex pathway allows cells to detect genomic damage and to mount an appropriate cellular response, from pausing the cell cycle and repairing DNA damage, to entering senescence, to undergoing apoptosis [1,2]. However, while many of the molecular components of the DDR are highly conserved across eukaryotic evolution, there is profound variation in how different cells respond to DNA damage based on such factors as signaling pathway status, tissue context, cell cycling status, development stage, and more [3][4][5][6][7][8][9][10]. Facing the same type and amount of DNA damage, cells in different contexts can vary widely in their propensity to undergo apoptosis in the face of DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the knowledge is accumulated that apoptosis is also induced by DNA damage [ 15 , 16 ]. Recently, Baonza et al reviewed about the genetic regulation leading to either apoptosis or non-apoptosis corresponding to the DNA damage induced by ionizing radiation in Drosophila [ 17 ]. However, to the best of our knowledge, no reports have comprehensively explored the direct relationship between apoptosis and somatic cell mutations induced by DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…1 . Moreover, it is well known that DNA repair system plays important roles in mutagenic process [ 1 ] and also apoptotic process is regulated by DNA repair [ 16 , 17 ]. Therefore, we examined how the DNA repair pathway influences apoptosis and mutation, and how apoptosis affects the behavior of mutated cells.…”
Section: Introductionmentioning
confidence: 99%